The Indonesian government’s coercive pressure on labour disclosures: conflicting interests or government ambivalence? - Cahaya, F.; Porter, Stacey; Tower, Greg; Brown, Alistair (© Emerald Group Publishing Limited, 2015)
Purpose: This paper aims to focus on corporate social responsibility and workplace well-being by examining Indonesian Stock Exchange (IDX)-listed companies’ labour disclosures. Design/methodology/approach: Year-ending 2007 and 2010 annual report disclosures of 31 IDX-listed companies are analysed. The widely acknowledged Global Reporting Initiative (GRI) guidelines are used as the disclosure index checklist. Findings: The results reveal that the overall labour disclosure level increases from 21.84 per cent in 2007 to 30.52 per cent in 2010. The levels of four of the five specific labour disclosures also increase with employment being the exception. The results further show that the Indonesian Government does not influence the increase in the levels of the overall labour disclosure or the four categories showing increased disclosure but, surprisingly, does significantly affect the decrease in the level of the employment category. Research limitations/implications: It is implied that the government is at best ambiguous given that, on one side, the government regulates all corporate social responsibility (CSR) activities and reporting but appears to coercively pressure companies to hide employment-specific issues. Practical implications: It is implied that Indonesian companies need to have “strong and influential” independent commissioners on the boards to counter any possible pressures from the government resulting in lower disclosure levels. Originality/value: This paper provides insights into the “journey” of labour-related CSR disclosure practices in Indonesia and contributes to the literature by testing one specific variant of isomorphic institutional theory, namely, coercive isomorphism.